Hubungan Kualitas Tidur dengan Hipertensi pada Lansia: Tinjauan Literatur - Izza Pramesthi; Farapti Farapti (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Hypertension is a major chronic disease among the elderly, influenced by modifiable lifestyle factors including sleep quality. Poor sleep quality in older adults is driven by age-related disruptions to circadian rhythms and melatonin production, worsened by chronic comorbidities. This literature review aimed to analyze the relationship between sleep quality and hypertension in the elderly. Articles were selected using the PRISMA flow diagram across three databases, Google Scholar, ScienceDirect, and PubMed with keywords related to sleep quality, hypertension, and the elderly. Methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Analytical Cross-Sectional Studies, with articles scoring ≥5 included in the review. From 3,821 identified articles, seven met the inclusion criteria and were analyzed descriptively. All seven studies used a cross-sectional design and measured sleep quality using the Pittsburgh Sleep Quality Index (PSQI). Results consistently showed that poor sleep quality was significantly associated with hypertension in the elderly, with the proportion of poor sleepers ranging from 50% to 74%. Physiologically, disrupted sleep impairs nocturnal blood pressure dipping through sympathetic activation, elevated cortisol, and HPA axis dysregulation, mechanisms further amplified by age-related vascular changes. These findings indicate that sleep quality should be treated as a modifiable risk factor in hypertension management, and routine sleep screening should be integrated into cardiovascular risk assessment in elderly care.